Matrykuła ziemska księstwa brzeskiego z początku XVIII w. = Estate Registry of the Duchy of Brzeg from the beginning of the 18th century - Kuczer, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The list of estates presented below has been the only known registry of property owners in the Duchy of Brzeg drawn up in the Duchy so far. It dates back to the beginning of the 18th century. However, the exact time of its origin is not known. It presents all forms of consignment, which are the emperor lists for parlicular duchies. The period which most of them come from is the last 70 years of ruling of the Habsburgs (from 1671 to 1738).
Keywords: Księstwo Brzeskie; spis dóbr; historia - 18 w.